The Relationship Between Problem–Focused Coping And Family Communication With Domestic Violence Against Women - Suryananda, Ida Ayu Indira Primaswari; Noviekayati, I Gusti Ayu Agung; Santi, Dyan Evita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study examines the relationship between Problem-Focused Coping and Family Communication with Domestic Violence (DV) against women. Problem-Focused Coping involves strategies to address violence through concrete solutions, while Family Communication refers to interactions to share information, express emotions, and resolve conflicts. Using a quantitative correlational method with 347 female DV victims, Spearman correlation analysis revealed significant positive relationships. Problem-focused coping had a correlation coefficient of 0.648 (p<0.05), and family communication had a coefficient of 0.359 (p<0.05), both indicating that higher levels of these variables were associated with increased DV. These findings rejected the hypotheses of negative relationships.